Analyzing how university is preparing engineering students for industry 4.0. - Jorge, Jéssica Mendes (2020)
Industry 4.0 is causing a lot of changes related to the way people work, bringing a demand for a new worker profile, mainly for engineers, that need to have not only technical skills but also methodological, social and personal skills. So, there is a need to study and identify how the university prepares engineering students for Industry 4.0 jobs. To achieve this objective a literature review was made, twenty nine skills of Industry 4.0 jobs were identified, and eight active learning methodologies were selected like paths that universities can use to develop skills for the Industry 4.0. To analyze how a university can use active learning methodologies to develop Industry 4.0 skills in engineering students, a questionnaire was applied in four engineering classes of the University of Brasilia, where the professors answered about the active learning methodology used and what skills were developed in the students, and the students answer the questionnaire with what skills they developed. A correlation analysis was applied to detect the different points of view between professors and students. Then, a decision tree was used to identify what skills were most developed by the active learning methodology used by the professor. The results show that are some divergences between the two points of view, and the questionnaire needs to be adaptable to measure with more reliability the skills that the professor wants to develop in each engineering class.